The Effectiveness of Role Playing Based Entrepreneurial Pedagogy Approach on The Values of Entrepreneurship in Elementary School (Universitas Negeri Semarang, 2019)
The purpose of this research was to analyze the effectiveness of role playing based entrepreneurial pedagogy approach on the values of entrepreneurship. The research method applied in this research was quantitative method of quasi-experimental with Nonequivalent Control Group Design model. Supported by observations conducted during the learning process by using role playing entrepreneurial pedagogy approach. Samples of this research were students of grade V of SDN Pelemkerep 1 and SDN Pelemkerep 2 in Jepara City. They were then divided into two groups of experimental design. SDN Pelemkerep 1 was taken as the experimental group using a role playing based on entrepreneurship pedagogy approach and SDN Pelemkerep 2 was taken as the control group using the expository method. The total number of sampel taken were 80 students. The technique of collecting data was done by using questionnaires and observation using indicators of creative, cooperative and independent. The results of the research showed that role playing based entrepreneurial pedagogy approach is effective in fostering the entrepreneurial values. It is indicated by the test results of independent sample t-test with (Sig. 0.000) smaller than 0.005. To support the data of questionnaire, the score acquire from the observation data showed a significant improvement with an excellent category for the experimental class in the 1st meeting at 38.95, 2nd meeting at 63.59, 3rd at 93.85. Role playing based entrepreneurial pedagogy approach can be using by teachers to inculcate entrepreneurial values implicitly in the learning process in the classroom in order to create fun and effective learning.